2018
DOI: 10.1097/md.0000000000011381
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of cardiac function in Duchenne and Becker muscular dystrophies on home mechanical ventilation

Abstract: Heart impairment is classical in dystrophinopathies and its management relies on medical drugs. Mechanical ventilation is used to treat respiratory failure, but can affect cardiac function. We aimed to investigate the natural history of cardiac function in patients with Duchenne (DMD) and Becker (BMD) muscular dystrophies on home mechanical ventilation (HMV).We reviewed the chart of DMD and BMD patients, followed in our institution, to obtain ventilation setting at HMV initiation and echocardiographic data at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Our study results also revealed a significant association between LVEF and lung volumes (FEV1 and FVC) along with a comparable rate of decline between LVEF and PFTs, in line with previous findings. 29 The limitations of this study include a small sample and short time intervals between the first and final visits. Systemic steroids are known to help preserve lung functions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our study results also revealed a significant association between LVEF and lung volumes (FEV1 and FVC) along with a comparable rate of decline between LVEF and PFTs, in line with previous findings. 29 The limitations of this study include a small sample and short time intervals between the first and final visits. Systemic steroids are known to help preserve lung functions.…”
Section: Discussionmentioning
confidence: 95%
“…Positive end‐expiratory pressure (PEEP) has been considered as a therapeutic option because PEEP can counteract intrathoracic volume loss and LV filling defect . Fayssoil et al . reported that patients with DMD with severe restrictive lung disease were also susceptible to LV systolic dysfunction and that, at lower tidal volume, LVEF declined rapidly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 24 papers studied more than 100 patients. 2,4,5,20,29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Of the 12 704 patients, 37% could be categorized as having ventilatory muscle weakness, 14% with chronic pulmonary disease, 10% with central hypoventilation, 9% with airway abnormalities, 6% with genetic/metabolic syndromes, 1% with cardiac/congenital heart disease, and 3% other/combined. Twenty percent of patients did not have a diagnosis reported.…”
Section: Resultsmentioning
confidence: 99%
“…While DMD is classically considered an X-linked recessive disease, the prevalence of de novo mutations has increased to 32 to 46% as routine anticipatory genetic counseling has decreased the incidence of DMD in families already affected by the disease [11]. Though classically seen to affect skeletal muscle, eventually, all muscles are affected, including respiratory, cardiac, and GI musculature [4,7,[12][13][14]. Diagnosis of DMD is presumptively made based on clinical presentation, with confirmation by genetic testing, and by biopsy if genetic tests are non-confirmatory [6,15].…”
Section: Discussion/observationsmentioning
confidence: 99%